Pengaruh Penggunaan Media Pembelajaran Visual Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP N 1 Sipoholon Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 (Jurnal Pendidikan Agama dan Teologi, 2023)
The purpose of this study is to determine the positive and significant influence of the use of visual learning media on the learning motivation of Christian Education students of Class VIII SMP N 1 Sipoholon, North Tapanuli Regency for the 2023/2024 Learning Year. The research method used is quantitative method with descriptive statistics. The population is all grade VIII students of SMP N 1 Sipoholon, North Tapanuli Regency for the 2023/2024 school year who are Protestant Christians as many as 160 students and a sample of 32 people was determined using purposive sampling techniques. Data was collected using a positive closed questionnaire of 50 items, namely 25 items for variable X and 25 items for variable Y. The results of the data analysis showed that there was a positive and significant influence on the use of visual learning media on the learning motivation of Christian Education students of Class VIII SMP N 1 Sipoholon, North Tapanuli Regency Learning Year 2023/2024: 1) Test analysis requirements: a) positive relationship test obtained rxy value = 0.500 > rtabel(=0.05,n=32) = 0.349. b) Significant relationship test obtained tcount value = 3.165 > ttable(=0.05,dk=n-2=30)= 2.042. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂="44.19"+0.47X. b) Regression coefficient of determination test (r2) = 25%. 3) Test the hypothesis using the F test obtained Fcalculate > Ftable=(=0.05,dk numerator k=22,dk denominator=n-2=32-2=30) which is 10.01 > 1.62. Thus Ha is accepted and H0 is rejected. So with this, it is expected that schools or teachers must use and further increase the use of Learning Media in schools because the use of learning media in the learning process affects student learning motivation.